Value of rhinitis vaccination of young pigs - Pollmann, D.S.; Schoneweis, D.A.; Kennedy, G.A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A study was conducted using 57 pigs from 10 litters to evaluate the value of rhinitis vaccination on performance, carcass quality, and health status. Pigs vaccinated with bordetella vaccine had fewer (P<.05) days to market and weight gains were superior (P<.05) to the non-vaccinated control group. Carcass quality and turbinate atrophy were not different among treatments. Turbinate scores were not related to growth rate.
Keywords: Swine; Rhinitis; Young pigs; Turbinate atrophy